2005
DOI: 10.1038/sj.cr.7290346
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of full-length C/EBPβ/liposome complex suppresses growth of human colon cancer in nude mice

Abstract: C/EBPβ (CCAAT/enhancer-binding protein β) is an important transcription factor involved in cellular proliferation and differentiation. Overexpression of the full-length C/EBPβ protein results in cellular growth arrest and apoptosis. Using a nonviral liposome as carrier, we delivered the full-length C/EBPβ expression plasmid, pCN, into nude mice bearing CW-2 human colon cancer tumors via tail vein. Southern blots revealed that the major organs and tumors were transfected. Experimental gene therapy showed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Seven candidate targets of miR-191 (unpublished and we are doing further research) were screened. C/EBPβ was chosen for further analysis, because previous reports have shown that C/EBPβ is an important regulator of cell growth [ 26 , 27 ], cell apoptosis [ 28 ] and tumorigenicity [ 29 ]. miR-191 has conserved binding sites in the 3′UTRs of C/EBPβ of different species (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven candidate targets of miR-191 (unpublished and we are doing further research) were screened. C/EBPβ was chosen for further analysis, because previous reports have shown that C/EBPβ is an important regulator of cell growth [ 26 , 27 ], cell apoptosis [ 28 ] and tumorigenicity [ 29 ]. miR-191 has conserved binding sites in the 3′UTRs of C/EBPβ of different species (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…2004). Overexpression of C/EBPβ induces apoptosis leading to suppression of colonic tumor growth in mice (Sun et al . 2005).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPb is also known to be involved in apoptosis (Mo et al 2004). Overexpression of C/EBPb induces apoptosis leading to suppression of colonic tumor growth in mice (Sun et al 2005). CHOP is a C/EBP homologous transcription factor (Yoshida et al 2005) and its activation induces astrocytic death in vitro following oxygen-glucose deprivation (Benavides et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPβ has been shown to be functional in the differentiation of adipocytes [18], uterine stromal cells [19], mammary epithelial cells [20] and hepatocytes [21]. Additionally, it was also shown that delivery of the full‐length C/EBPβ gene in nude mice suppressed the growth of colonic tumors by inducing apoptosis [22].…”
Section: Introductionmentioning
confidence: 99%